2014
DOI: 10.1039/c3ee43991g
|View full text |Cite
|
Sign up to set email alerts
|

Investigating charge dynamics in halide perovskite-sensitized mesostructured solar cells

Abstract: Evidence of complementary carrier percolation paths in halide perovskite-sensitized mesostructured solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
148
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(161 citation statements)
references
References 40 publications
10
148
3
Order By: Relevance
“…To the best of our knowledge, TPV data have not been published on CH 3 NH 3 PbI 3− X Cl X PSCs employing a mesoporous alumina scaffold, however several studies have considered photovoltage decay behavior in CH 3 NH 3 PbI 3 PSCs employing a mesoporous TiO 2 scaffold. [ 39,56,57 ] Critically, TPV decays in these device architectures were strongly biexponential, in contrast to the monoexponential behavior apparently observed here. O'Regan et al proposed that under 1 sun conditions, photovoltage decays with a lifetime of around 1 μs correspond to the dominant electron/hole recombination channel.…”
Section: Resultscontrasting
confidence: 47%
See 1 more Smart Citation
“…To the best of our knowledge, TPV data have not been published on CH 3 NH 3 PbI 3− X Cl X PSCs employing a mesoporous alumina scaffold, however several studies have considered photovoltage decay behavior in CH 3 NH 3 PbI 3 PSCs employing a mesoporous TiO 2 scaffold. [ 39,56,57 ] Critically, TPV decays in these device architectures were strongly biexponential, in contrast to the monoexponential behavior apparently observed here. O'Regan et al proposed that under 1 sun conditions, photovoltage decays with a lifetime of around 1 μs correspond to the dominant electron/hole recombination channel.…”
Section: Resultscontrasting
confidence: 47%
“…O'Regan et al proposed that under 1 sun conditions, photovoltage decays with a lifetime of around 1 μs correspond to the dominant electron/hole recombination channel. [ 39 ] The physical location of this recombination process was not confi rmed, however related work suggested that the long-lifetime decay component relates to charge recombination within the TiO 2 scaffold [ 56,57 ] with the shorter component (up to several microseconds) quantifying carrier lifetime within the perovskite layer. Although we caution against the comparison of absolute TPV decay times between independent studies, due to likely variations in device preparation and measurement conditions, in our solar cells the volume fraction of TiO 2 is relatively low because the metal oxide exists as a compact cathode interface layer only.…”
Section: Resultsmentioning
confidence: 99%
“…7). The PL quenching measurements are related to the electron-hole diffusion lengths and lifetimes 37,38 . As shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There is also debate about how to correctly measure the recombination and transport times, the charge density, and even the correct measurement of efficiency. [5][6][7][8][9][10][11][12][13][14][15][16][17] The debate about characterization centers on the interpretation of various time constants that can be measured by optical and electrical means. These time constants range from <1 µs to >100 µs.…”
Section: Introductionmentioning
confidence: 99%